EFFECT OF INCORPORATION OF FERMENTED BAMBOO SHOOT, BEET ROOT AND CABBAGE ON THE QUALITIES OF CHICKEN NUGGETS UNDER FROZEN STORAGE - S. Doley; K. Kikhi; A. Sen; S. Ghatak; S. Kumar; G. Khargharia (Indian Journal of Veterinary and Animal Sciences Research, 2023)
Chicken nuggets prepared from spent hens’ meat by incorporating fermented bamboo shoots at 10 per cent, beet root at 10per cent and cabbage at 15per cent levels were evaluated for different physicochemical, microbial and sensory qualities under frozen (-18±1°C) storage condition. The pH of all nuggets increased significantly (P<0.05) during the storage period. The hardness, redness (a*), yellowness (b*) and chromavalues of all the nuggets decreased significantly (P<0.05) during storage period. The ΔE values of all the nuggets increased during storage period. There was no growth of microorganisms in all the nuggets during the period. The beet root incorporated nuggets recorded better sensory qualities compared to other nuggets in the study under frozen (-18±1°C) storage up to 90 days.